Primary Actinomycosis in the breast caused by Actinomyces neuii. A report of 2 cases. (2017) - Leenstra, B.S.; Schaap, C.C.M.; Bessems, M.; Renders, N.H.M.; Bosscha, K.
Abstract: Actinomycosis is a slowly progressive infection caused by anaerobic bacteria, primarily from the genus Actinomyces . Primary actinomycosis of the breast is rare and presents as a mass like density which can mimic malignancy. Mammography, ultrasonography and histopathologic examination is required for diagnosis. Treatment should consist of high doses of antibacterials for a prolonged period of time and possibly surgical drainage. Primary actinomycosis infections are commonly caused by A. israelii . Actinomyces neuii is a less common cause of classical actinomycosis. We present two cases of primary actinomycosis of the breast in two female patients caused by A. neuii.